The Korean economy at the crossroads - Tcha, MoonJoong, 1961-; Sŏ, Chung-sŏk, 1957-2015 (RoutledgeCurzon studies in the growth economies of Asia, 2003)
The book covers the origin and evolution of the Korean economic system, special factors including chaebols, Korean industries since the crisis, what happened to the money after the capital flight of the crisis and asks did the USA benefit?